Study of the diagnostic and prognostic value of parameters of cytokine profile, oxidative stress and cytogenetic abnormalities in patients with tick-borne infections - E. N. Ilyinskikh; O. V. Voronkova; K. V. Samoylov; A. V. Semenova; R. R. Hasanova; Yu. I. Bulankov; V. N. Nekrasov; E. I. Petrova; G. N. Kolganova (Журнал инфектологии, 2024)
Objective: is to assess parameters of cytokine profile, and some biomarkers of hemogram, cytogenetic damage, and oxidative stress to determine their associations with clinical symptoms and identify early prognostic factors for tick-borne encephalitis febrile form compared with Lyme borreliosis non-erythemal form at the onset of the disease.Materials and methods. In 25 patients with febrile tickborne encephalitis (mean age: 49.51 years), 24 patients with Lyme borreliosis non-erythemal form (mean age: 46.70 years) and 14 healthy donors (mean age: 47.20 years), the following parameters were analyzed: hemogram, blood leukocyte indices, cytokine profile, the levels of micronucleated T-lymphocytes, malondialdehyde and total immunoglobulin (Ig) G. For statistical analysis, the Mann–Whitney U-test, Pearson’s goodness-of-fit test, Spearman’s correlation coefficient, and ROC assay with AUC assessment were used.Results. In the tick-borne encephalitis patient group compared to the controls, the following parameters were increased: neutrophil count, blood leukocyte indices, the levels of micronucleated T-lymphocytes, malondialdehyde and proinflammatory cytokines in the blood, which directly correlated with maximal pyrexia levels. Prognostic value for early preliminary diagnosis of tick-borne encephalitis compared with borreliosis showed the following blood parameters: increases in neutrophil count and the levels of micronucleated T-cells, neutrophils to monocytes ratio, neutrophils to lymphocytes ratio, concentrations of malondialdehyde, tumor necrosis factor (TNF)-α, interleukins (IL)-8, IL-6, IL-10, and TNF-α/IL-4 ratio as well as decreases in the levels of IL-4 and total serum IgG. The parameters showed from average to excellent predictive ability as well as high positive and negative predictive values.Conclusion. In patients with tick-borne encephalitis, we detected correlations between the pyrexia levels and the biomarkers of inflammation, oxidative stress, and cytogenetic damage as well as it were found some differences in these parameters from the group of borreliosis patients, which probably had prognostic significance.